Colloidal Synthesis of Silicon–Carbon Composite Material for Lithium‐Ion Batteries. Issue 36 (31st July 2017) - Su, Haiping; Barragan, Alejandro A.; Geng, Linxiao; Long, Donghui; Ling, Licheng; Bozhilov, Krassimir N.; Mangolini, Lorenzo; Guo, Juchen
Abstract: We report colloidal routes to synthesize silicon@carbon composites for the first time. Surface‐functionalized Si nanoparticles (SiNPs) dissolved in styrene and hexadecane are used as the dispersed phase in oil‐in‐water emulsions, from which yolk–shell and dual‐shell hollow SiNPs@C composites are produced via polymerization and subsequent carbonization. As anode materials for Li‐ion batteries, the SiNPs@C composites demonstrate excellent cycling stability and rate performance, which is ascribed to the uniform distribution of SiNPs within the carbon hosts. The Li‐ion anodes composed of 46 wt % of dual‐shell SiNPs@C, 46 wt % of graphite, 5 wt % of acetylene black, and 3 wt % of carboxymethyl cellulose with an areal loading higher than 3 mg cm −2 achieve an overall specific capacity higher than 600 mAh g −1, which is an improvement of more than 100 % compared to the pure graphite anode. These new colloidal routes present a promising general method to produce viable Si–C composites for Li‐ion batteries. Abstract : Electrode materials : Two novel routes have been developed to synthesize Si–C composites from colloidal systems. Superior Li‐ion anode performance was achieved, attributed to the uniform dispersal of Si nanoparticles in the secondary carbon structure.